Midwives Working During COVID-19 Pandemic and Anxiety - nurrasyidah, rahmi (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
Conducive workplace affects the anxiety level of health workers. This article reviews the association between the midwife's workplace, availability of personal protective equipment and length of work with midwife’s anxiety. This is a cross-sectional study, conducted in January-December 2021, located in Klaten, Sample recruited in this study was 135 midwives by stratified random sampling. The midwife's workplace, duration of work time and availability of Personal Protective Equipment were not related to midwifery anxiety. Further research needs to be done with a larger sample size using the case-control or cohort method.